2020
DOI: 10.2345/0899-8205-54.6.418
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH : Evaluation of Orthopedic Hip Device Recalls by the FDA from 2007 to 2017

Abstract: Background: Medical device recalls have increased in the previous two decades. Orthopedic devices are estimated to constitute 12% of all medical devices recalled. Medical devices enter the market via the Food and Drug Administration's (FDA's) premarket approval (PMA) or 510(k) pathways. This article evaluates orthopedic hip device recalls between Jan. 1, 2007, and Dec. 31, 2017. We hypothesized that the 510(k) approval process would have substantially higher recall rates for defective devices. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Whilst post-market surveillance is designed to detect only the most severe adverse outcomes, which are just a fraction of adverse outcomes that matter to patients (3;39). Furthermore, clinicians and patients are not readily made aware of evidence regarding a device's poor safety record, as demonstrated by Peters, Pellerin, and Janney, whose study showed that recalls of Class III devices in the US took more than 8 months to complete (40). Several authors have also demonstrated that although a device has been recalled it may still be used as a predicate (i.e., a substantially equivalent, legally marketed) device to support the market authorization of many subsequent devices through equivalence claims (38;41-44).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst post-market surveillance is designed to detect only the most severe adverse outcomes, which are just a fraction of adverse outcomes that matter to patients (3;39). Furthermore, clinicians and patients are not readily made aware of evidence regarding a device's poor safety record, as demonstrated by Peters, Pellerin, and Janney, whose study showed that recalls of Class III devices in the US took more than 8 months to complete (40). Several authors have also demonstrated that although a device has been recalled it may still be used as a predicate (i.e., a substantially equivalent, legally marketed) device to support the market authorization of many subsequent devices through equivalence claims (38;41-44).…”
Section: Discussionmentioning
confidence: 99%